Vestibular migraine and its management in Indian clinical setting: a narrative review - M., Ilambarathi; Bijlani, Avinash; Roy, Dhrubo (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Vestibular migraine (VM) is a disorder connecting two clinical conditions, migraine and vertigo. A high prevalence of VM (~30%) is reported among Indians suffering from dizziness. Yet, there is no gold standard for diagnosis and treatment. Trials specifically for patients with VM are scarce. This review provides an overview on VM and its management in the Indian clinical setting. An evidence-based discussion and review of literature on VM was performed by expert panelists, and opinions were gathered. Experts opined that in vertigo clinics, around 50% of patients are diagnosed with VM, with a higher predominance in females aged 30-50 years, while in children, the age of manifestation is 12-14 years. The most common presenting symptoms of VM among adults are spontaneous vertigo, followed by positional vertigo with headache, nausea, vomiting, photophobia and phonophobia, while intolerance to loud sounds and sudden falls are common symptoms in children with VM. Common comorbidities associated with VM are benign paroxysmal positional vertigo (BPPV) and Meniere’s disease (MD). Experts opined that there are currently no approved standardized treatment protocols for VM. The steps in the management of VM include diet and lifestyle modification, along with medicines for symptomatic relief (abortive) and prophylaxis and vestibular rehabilitation. Globally, prochlorperazine, a vestibular suppressant, is widely used for the management of vertigo and its associated symptoms. According to experts, prochlorperazine 5 mg twice or thrice daily for 5-7 days can play a significant role as an abortive treatment in the management of various patient profiles of VM.